The Inverse Correlation Between the Duration of Lifetime Occupational Radiation Exposure and the Prevalence of Atrial Arrhythmia - Thirumal, Rithika; Vanchiere, Catherine; Bhandari, Ruchi; Jiwani, Sania; Horswell, Ronald; Chu, San; Chamaria, Surbhi; Katikaneni, Pavan; Boerma, Marjan; Gopinathannair, Rakesh; Olshansky, Brian; Bailey, Steven; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective Advancements in fluoroscopy-assisted procedures have increased radiation exposure among cardiologists. Radiation has been linked to cardiovascular complications but its effect on cardiac rhythm, specifically, is underexplored. Methods Demographic, social, occupational, and medical history information was collected from board-certified cardiologists via an electronic survey. Bivariate and multivariable logistic regression analyses were performed to assess the risk of atrial arrhythmias (AA). Results We received 1,478 responses (8.8% response rate) from cardiologists, of whom 85.4% were male, and 66.1% were ≤65 years of age. Approximately 36% were interventional cardiologists and 16% were electrophysiologists. Cardiologists > 50 years of age, with > 10,000 hours (h) of radiation exposure, had a significantly lower prevalence of AA vs. those with ≤10,000 h (11.1% vs. 16.7%, p = 0.019). A multivariable logistic regression was performed and among cardiologists > 50 years of age, exposure to > 10,000 radiation hours was significantly associated with a lower likelihood of AA, after adjusting for age, sex, diabetes mellitus, hypertension, and obstructive sleep apnea (adjusted OR 0.57; 95% CI 0.38–0.85, p = 0.007). The traditional risk factors for AA (age, sex, hypertension, diabetes mellitus, and obstructive sleep apnea) correlated positively with AA in our data set. Cataracts, a well-established complication of radiation exposure, were more prevalent in those exposed to > 10,000 h of radiation vs. those exposed to ≤10,000 h of radiation, validating the dependent (AA) and independent variables (radiation exposure), respectively. Conclusion AA prevalence may be inversely associated with radiation exposure in Cardiologists based on self-reported data on diagnosis and radiation hours. Large-scale prospective studies are needed to validate these findings.